Potential of red dragon fruit peel extract gel (hylocereus polyrhizus) as a disclosing agent to detect bacterial plaque - Nicolas, Kevin; Suwandi, Trijani (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Bacterial plaque is one of the sources of oral health problems that can cause cavities and periodontal disease. One way to minimize the risk of dental and oral diseases is to carry out good and proper plaque control. Plaque control can be supported by the use of disclosing agents that visualize bacterial plaque well so as to increase motivation and education in the community to evaluate their oral hygiene. Objectives: This article reviews the use of disclosing agents with natural ingredients as one of alternative choices that can be used to prevent harmful side effects from certain synthetic dyes, such as erythrosine. Literature review: One example of a natural ingredient that can be used as a natural dye is the red dragon fruit peel (Hylocereus polyrhizus) through the maceration method to produce a disclosing agent in the form of a gel preparation. Conclusion: After going through a series of preparation tests on the gel formulation, it was concluded that the red dragon fruit peel extract formulation has the potential as a disclosing agent to visualize bacterial plaque in the oral cavity well.